The Prevalence of Complementary and Alternative Medicine used in Postmenopausal Women at Srinagarind Hospital - Nisanat Booning; Sukree Soontrapa; Srinaree Kaewrudee; Chompilas Chongsomchai; Bandit Chumworathayi; Teerayut Temtanakitpaisan (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To study the prevalence, types, sources of information, and physicians' awareness regarding the usage of complementary and alternative medicine (CAM) in postmenopausal women at Srinagarind Hospital.Study design: Cross sectional descriptive study.Materials and methods: A survey was conducted between July and October 2013 in 200 postmenopausal women with general gynecologic problems who attended the outpatient department of Obstetrics and Gynecology, Srinagarind Hospital, a tertiary care hospital, in northeastern Thailand. Validated questionnaires for determining the prevalence, types, sources of information, and awareness of the physicians in CAM were used.Results: The mean age of the participants was 56.1 years. The prevalence of current CAM use was 63.0%. Ya satree was the most commonly used (18.6%) followed by fermented herb juice (16.5%) and chlorophyll (13.1%). The most important sources of information of participants in deciding to use CAM was the recommendation of acquaintances or friends (79.4%) followed by advertisements in newspaper or magazine (16.7%) and advertising on television (13.5%). Only 28.0% and 19.5% of the participants were asked by the physician about their history of CAM use and informed by the physician about the potential risk of CAM such as herb-drug interaction and adverse effects, respectively.Conclusions: More than 60% of postmenopausal women interviewed at Srinagarind Hospital used CAM. Most participants (72%) never had asked about their history of CAM use by the physician. More education on this issue should be provided to patients in order to reduce unnecessary CAM used, and CAM used should be a part of routine history taking in all patients.